Editorial: re‐thinking cardiovascular risk factors in NAFLD with advanced fibrosis?. Issue 10 (27th April 2020) - Horn, Paul; Newsome, Philip N.
Abstract : LINKED CONTENT This article is linked to Henson et al and Henson and Corey papers. To view these articles, visit https://doi.org/10.1111/apt.15660 and https://doi.org/10.1111/apt.15696 .